Employing a Fixed-Lean Multiple Schedule in the Treatment of Challenging Behavior for Children With Autism Spectrum Disorder. Issue 4 (July 2018) - Haq, Shaji S.; Machalicek, Wendy; Garbacz, S. Andrew; Drew, Christine
Despite its utility, there is limited applied research on employing fixed-lean (FL) schedules of reinforcement in treatment packages to address challenging behavior. One potential reason is that abrupt shifts to terminal schedules of reinforcement have been associated with immediate increases in challenging behavior before subsiding to clinically acceptable levels. The purpose of the present study was to (a) provide evidence demonstrating the utility of a FL multiple schedule (MS) in the treatment of challenging behavior in applied settings, (b) examine the potential effects of alternative stimuli on challenging behavior during a FL MS, and (c) assess the social validity of this treatment package with participants and caregivers. The results of this study showed low levels of challenging behavior and discriminated mands during the FL MS, but no evidence to support the inclusion of alternative stimuli. In addition, caregivers of both participants reported high levels of satisfaction with the treatment package. Implications for research and clinical practice are discussed.